SYNTHESIS AND CHARACTERIZATION OF BISMUTH-BASED HYDROXYAPATITES DOPED WITH CERIUM - KAREEM, REBAZ OBAID (Fırat Üniveristesi, 2023)
Bu çalışma, Ce katkılı Bi-esaslı hidroksiapatitlerin (HAp) teorik ve deneysel karakterizasyonlarını ele almaktadır. Beş Bi-esaslı numune (% 0.125 sabit miktarda) çeşitli miktarlarda (0, 0.125, 0.25, 0.375 ve 0.500 at. %) Ce ilavesiyle yaş kimyasal yöntem kullanılarak sentezlendi. Hazırlanan numuneler X-ışını kırınımı (XRD), taramalı elektron mikroskopisi (SEM), Fourier dönüşümlü kızılötesi (FTIR) spektroskopisi, Raman spektroskopisi, diferansiyel termal analiz (DTA), termogravimetrik analiz (TGA) ve titreşimli numune manyetometresi ile deneysel olarak incelenmiştir (VSM). Ayrıca, tüm numuneler yoğunluk fonksiyonel teorisi (DFT) kullanılarak modellenmiş ve teorik sonuçlar elde edilmiştir. Hem deneysel hem de teorik sonuçlar, örgü parametrelerinin ve birim hücre hacminin Ce içeriğinden önemli ölçüde etkilendiğini göstermiştir. Numunelerin hesaplanan bant aralığı enerjileri kademeli olarak 4.6308 eV'den 4.5299 eV'ye düştü. Durum yoğunlukları (DOS) da Ce miktarından etkilenmiştir. 0.500 at. % Ce katkılı numunenin, sentezlenen tüm numuneler arasında en iyi biyouyumluluğu gösterdiği bulundu. Lineer absorpsiyon katsayısı artan foton enerjisi ile azalırken, artan Ce miktarı ile artar. Yoğunluk artan Ce içeriğiyle 3.1615 g cm-3 ten 3.1772 g cm-3'e artar. Artan Ce miktarı ile hem kristal büyüklüğü hem de kristalleşme giderek azalmıştır. FTIR ve Raman spektrumları, tüm numuneler için HAp yapısının oluşumunu doğrular.

This study deals with the theoretical and experimental characterizations of Bi-based hydroxyapatites (HAp) doped with Ce. Five samples of Bi-based HAp (at a constant amount of 0.125 at.%) with the addition of the Ce in various amounts (0, 0.125, 0.25, 0.375, and 0.500 at. %) were synthesized by using the wet chemical method. The prepared samples were investigated experimentally by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transforms infrared (FTIR) spectroscopy, Raman spectroscopy, differential thermal analysis (DTA), thermogravimetric analysis (TGA), and vibrating sample magnetometer (VSM). All the samples were also modeled by using a density functional theory (DFT), and theoretical results were obtained. Both experimental and theoretical results showed that the lattice parameters and unit cell volume were significantly affected by Ce content. The calculated bandgap energies of the samples gradually decreased from 4.6308 eV to 4.5299 eV. The density of states (DOS) were also affected by the amount of Ce. It was found that the sample doped with 0.500 at. % Ce showed the best biocompatibility among all the as-synthesized samples. The linear absorption coefficient increased with increasing amounts of Ce, while this decreased with increasing photon energy. The density increases ranging from 3.1615 g cm-3 to 3.1772 g cm-3 with the increasing Ce content. Both crystallite size and crystallinity gradually reduced with the increasing amount of Ce. FTIR and Raman spectra confirm the formation of the HAp structure for all the samples.
Bizmut esaslı seryum katkılı hidroksiapatitlerin sentez ve karakterizasyonu
Keywords: Fizik ve Fizik Mühendisliği